Research progress on screening and evaluation tools for frailty - ZHANG Yin′en; WANG Jianlong; YU Huanhuan; ZHANG Pu; MA Xiang; MA Zheng; JIAO Jianbao (Zhongguo linchuang yanjiu, 2023)
Frailty is defined as a condition of reduced physiological reserves. When the elderly is exposed to stressors, it will lead to a state of weakness and increase the risk of adverse health consequences. Early screening of frailty and early intervention can significantly reduce the incidence of adverse consequences, while evaluating the state of patients in frailty can develop more reasonable intervention strategies. This article reviewed the content, clinical application, advantages and disadvantages of frailty screening tools and evaluation tools, aiming at early screening, evaluation of patients with frailty and early intervention, helping clinical decision-making and management of elderly patients with frailty, selecting suitable screening and evaluation tools for patients, and reducing the incidence of a series of adverse consequences.